Induced Ferromagnetism in Epitaxial Uranium Dioxide Thin Films - Yogesh Sharma; Binod Paudel; Amanda Huon; Matthew M. Schneider; Pinku Roy; Zachary Corey; Rico Schönemann; Andrew C. Jones; Marcelo Jaime; Dmitry A. Yarotski; Timothy Charlton; Michael R. Fitzsimmons; et al. (Advanced Science, 2022)
Abstract Actinide materials have various applications that range from nuclear energy to quantum computing. Most current efforts have focused on bulk actinide materials. Tuning functional properties by using strain engineering in epitaxial thin films is largely lacking. Using uranium dioxide (UO2) as a model system, in this work, the authors explore strain engineering in actinide epitaxial thin films and investigate the origin of induced ferromagnetism in an antiferromagnet UO2. It is found that UO2+x thin films are hypostoichiometric (x<0) with in‐plane tensile strain, while they are hyperstoichiometric (x>0) with in‐plane compressive strain. Different from strain engineering in non‐actinide oxide thin films, the epitaxial strain in UO2 is accommodated by point defects such as vacancies and interstitials due to the low formation energy. Both epitaxial strain and strain relaxation induced point defects such as oxygen/uranium vacancies and oxygen/uranium interstitials can distort magnetic structure and result in magnetic moments. This work reveals the correlation among strain, point defects and ferromagnetism in strain engineered UO2+x thin films and the results offer new opportunities to understand the influence of coupled order parameters on the emergent properties of many other actinide thin films.